Optimization of Anthocyanin Extraction from Cockspur Coral (Erythrina Crista-Galli L.) Petals with Microwave-Assisted Extraction (MAE) using Response Surface Methodology - Astrilia Damayanti; Bayu Triwibowo; Megawati Megawati; Miftahuddin Azhari; Sandra Anggita Fadriana (Department of Chemical Engineering, Universitas Gadjah Mada, 2021)
Cockspur coral (Erythrina crista-galli L) petals are flowers that contain anthocyanins and active compounds of flavonoids and tannins. This study aims to determine the optimum conditions for the anthocyanin extraction process of cockspur coral petals using Microwave-Assisted Extraction (MAE), analyzed through the Response Surface Method (RSM). This process uses ethanol-hydrochloric acid solvents and a Box-Behnken experimental design involving three factors, namely the solvent ratios (w/v) (1:5, 1:15, and 1:25), microwave powers (300, 450, and 600 watts), and extraction times (3, 9, and 15 minutes). As a result, the second-order polynomial model was enhanced and sufficient to explain the variation of the data that denoted the significant correlation with the independent variables and the response. Derringer's desired function methodology was used for optimizing studies and generated ideal conditions for each or combined an independent variable. The optimum anthocyanin extract of 5.82 mg/L was obtained at a power condition of 325,5 Watts, an extraction time of 3.05 minutes, and a solvent ratio of 20.5. Meanwhile, the operating conditions at a power of 310.8 Watts, a time of 14.94 minutes, and a solvent ratio of 24.96 resulted in the optimum color intensity (IC) of 1040.26. In the meantime, the optimum antioxidant activity was obtained at a power of 585.97 Watts, a time of 4.93 minutes, and a solvent ratio of 5.43 with IC50 of 0.115.